Health and performance of zebu cattle exposed to trypanosomiasis risk in S.W. Ethiopia - Mulatu, W.; D'Ieteren, G.D.M.; Duffera, W.; Girma, T.; Itty, P.; Leak, S.G.A.; Maehl, J.H.H.; Nagda, S.M.; Paling, R.W.; Rarieya, J.M.; Thorpe, W.R.; Trail, J.C.M. (International Livestock Centre for Africa, 1988)
Reports the results of an 18-month study on the prevalence, species and intensity of trypanosome parasitaemias in East African Zebu cattle managed in ten village herds in four areas around Ghibe, S.W. Ethiopia. Gives an estimation of tsetse related density and trypanosome infection rates in tsetse, reports the effects of trypanosome infection on PCV, and includes some preliminary performance results.